Bile duct penetrating duodenal wall sign: a novel computed tomography finding of common bile duct stone impaction into duodenal major papilla - Shintani, Shuhei; Inatomi, Osamu; Bamba, Shigeki; Imai, Takayuki; Tomozawa, Yuki; Inoue, Akitoshi; Ota, Shinichi; Takeda, Yoshiya; Fujimoto, Takehide; Nishida, Atushi; Kutsumi, Hiromu; Watanabe, Yoshiyuki; et al. (Japanese journal of radiology, 2023)
Purpose Impacted common bile duct stones cause severe acute cholangitis. However, the early and accurate diagnosis, especially iso-attenuating stone impaction, is still challenging. Therefore, we proposed and validated the bile duct penetrating duodenal wall sign (BPDS), which shows the common bile duct penetrating the duodenal wall on coronal reformatted computed tomography (CT), as a novel sign of stone impaction. Methods Patients who underwent urgent endoscopic retrograde cholangiopancreatography (ERCP) for acute cholangitis due to common bile duct stones were retrospectively enrolled. Stone impaction was defined by endoscopic findings as a reference standard. Two abdominal radiologists blinded to clinical information interpreted CT images to record the presence of the BPDS. The diagnostic accuracy of the BPDS to diagnose stone impaction was analyzed. Clinical data related to the severity of acute cholangitis were compared between patients with and without the BPDS. Results A total of 40 patients (mean age 70.6 years; 18 female) were enrolled. The BPDS was observed in 15 patients. Stone impaction occurred in 13/40 (32.5%) cases. Overall accuracy, sensitivity, and specificity were 34/40 (85.0%), 11/13 (84.6%), and 23/27 (85.2%), respectively; 14/16 (87.5%), 5/6 (83.3%), and 9/10 (90.0%) for iso-attenuating stones; and 20/24 (83.3%), 6/7 (85.7%), and 14/17 (82.4%) for high-attenuating stones. Interobserver agreement of the BPDS was substantial ( κ = 0.68). In addition, the BPDS was significantly correlated with the number of factors in the systemic inflammatory response syndrome ( P = 0.03) and total bilirubin ( P = 0.04). Conclusion The BPDS was a unique CT imaging finding to identify common bile duct stone impaction regardless of stone attenuation with high accuracy.